Food and Beverage Promotion Strategy to Increase Sales, at PT. Reska Multi Business - Suparna Suparna; Muinah Fadhilah (Return : Study of Management, Economic and Bussines, 2023)
Technological developments are very fast like today. Making companies have to be able to face competition and be able to win the market. There is a lot of competition for food and beverage service and sales made.  PT. Reska Multi Usaha is a challenge. For this reason, PT Reska Multi Usaha always innovates so that it can. Serve consumers, as well as keep abreast of technological developments and services that move dynamically. For example, providing discounts, making Indonesian food, holding events, and making sales applications to offer products to the public. The purpose of this research is to determine the level of achievement of service, sales, and promotion through sales and promotion mix in service improvement and sales achievement by using the lokomart.id application and promotions through advertising, price discounts, individual sales, direct sales, and sales with application theory. This research method is a quantitative method with a descriptive approach, through in-depth interviews and documents relevant to the research. the subjects of this study were area 6 Yogyakarta managers, junior sales managers, senior sales supervisors, and sales staff.  PT. Reska multi Usaha formed a forum for sales communication and promotion of food and beverage products through 1. Advertising, with railroad television, raw food, kai access, and the official lokomard.id.website. 2. Sales promotion using discounted prices, vouchers, to users, or purchases through kai access and lokomard.id.3.sales promotion by holding events at the station, educational tours, and public relations. 4. face-to-face individual sales to get feedback, 5. Marketing and direct sales and. 6. Digital marketing to find out direct responses from consumers.